2021
DOI: 10.2196/24165
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of COVID-19 Emergency Alert Text Messages on Practicing Preventive Behaviors: Cross-sectional Web-Based Survey in South Korea

Abstract: Background Sending emergency messages via mobile phone text messaging can be a promising communication tool to rapidly disseminate information and promote preventive behavior among the public during epidemic outbreaks. The battle to overcome COVID-19 is not yet over; thus, it is essential that the public practices preventive measures to prevent the spread of COVID-19. Objective This study aimed to investigate the effectiveness of reading and obtaining i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Gender has emerged as a significant issue during this pandemic. Previous studies have shown that women are more likely to engage in preventive behaviors [42][43][44]; however, they are less willing than men to receive the vaccine [29], with more females declaring that they are unsure of taking the vaccine. Similarly, our study results reveal that women (224/1016, 45.2%) are more hesitant to receive COVID-19 vaccination than men (317/1016, 61%).…”
Section: Principal Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gender has emerged as a significant issue during this pandemic. Previous studies have shown that women are more likely to engage in preventive behaviors [42][43][44]; however, they are less willing than men to receive the vaccine [29], with more females declaring that they are unsure of taking the vaccine. Similarly, our study results reveal that women (224/1016, 45.2%) are more hesitant to receive COVID-19 vaccination than men (317/1016, 61%).…”
Section: Principal Resultsmentioning
confidence: 99%
“…Moreover, in Korea, face masks were promoted based on substantial relative benefits, high efficacy of slowing viral spread, and low cost. Several studies report high compliance and high efficacy beliefs on wearing masks among the Korean population [42][43][44]. Therefore, people might prefer to wear face masks over vaccination to avoid the risk of the side effects from vaccination.…”
Section: Principal Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gozzi et al (2020) found that user activity on Reddit and active search on Wikipedia pages about COVID-19 are primarily driven by media coverage. Lee and You (2021) found that in addition to social media or legacy media, the warning text messages were also proved to be an effective way for enhancing protective behaviors in the pandemic.…”
Section: Review Resultsmentioning
confidence: 99%
“…Lee et al explored the effectiveness of obtaining information through emergency warning SMS in the early stage of the COVID-19 outbreak in South Korea and its impact on individual prevention behavior. They believe that the government should actively consider sending emergency warning messages to provide accurate and reliable information to the public, which is conducive to reducing the impact of negative news [ 42 ].…”
Section: Discussionmentioning
confidence: 99%